Farmers perspectives on climate change in northern region of Nigeria - AdamuNdawayo, Buba; Shamsudin, Mad Nasir; Radam, Alias; Abdullah, Ahmad Makmom (International Organization of Scientific Research, 2017)
Climate distribution of Nigeria comprehend several vegetation belt as you move northward from the coast, northern region of Nigeria were predominantly agrarian by occupation due to their geographical location having two distinct seasons of wet and dry season. Recently there has been a global debate on climate change and its possible consequences around the world, the effects may varied based on the adaptive capacity of every region on earth, but most studies indicate the possible consequences effect on crop production particularly in sub Saharan Africa which Nigeria is included. This study was conducted to understand the level of farmers’ awareness towards climate change in the region of northern Nigeria and how they perceived climate change would affect their occupation.